Revolusi Nilai Multikultural di Pondok Pesantren Al-Barokah: Perspektif Santri dan Tantangan pada Era 5.0 - Dianita, Galuh; ‘Aliyah, Naily Khuriyatul (Edukhasi: Jurnal Inovasi Pendidikan, 2024)
Fostering the multicultural life of students in the context of the industrial revolution 5.0 is an important aspect in Islamic boarding schools, because it provides provisions for students to face the challenges that occur in the diversity around their environment and face a society that goes hand in hand with technological sophistication. This research uses qualitative research by utilizing primary data sources and secondary data sources. Primary sources come directly from sources through interviews, while secondary sources include the history of the Al-Barokah Islamic Boarding School and data on infrastructure. The techniques used to explore data sources are interviews, observation and documentation with John Cresswel's analysis. This research found that the implementation of multicultural values ​​carried out by students in the Al-Barokah Islamic Boarding School environment includes mutual respect, mutual respect, mutual understanding, tolerance, not making fun of other students and learning from each other between cultures. Solutions for strengthening multicultural values ​​in the 5.0 era include an inclusive curriculum, holding joint activities, using technology for multicultural education, empowering students, and self-assessing the implementation of multicultural values. Even though global developments are increasingly rapid, Islamic boarding schools are expected to not only maintain the authenticity of Islamic traditions, but also innovate in responding to the dynamics of an increasingly multicultural society.